1996
DOI: 10.1159/000117294
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Carbon Disulfide Encephalopathy

Abstract: To understand central nervous damage after long-term exposure to carbon disulfide (CS2), 10 patients who had polyneuropathy with various neuropsy-chiatric symptoms in a viscose rayon plant were studied. Clinical and laboratory examinations including electroencephalography (EEG), brain computed tomography (CT), brain magnetic resonance images (MRI), and carotid duplex sonography were carried out. Clinically, headache, unpleasant dreams, memory impairment, fatigue, anorexia and emotional lability were common in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…In the patient described, both CT and MRI showed a picture of diffuse and progressive encephalic atrophy which was particularly pronounced in the cerebellum, according with the clinical picture. Focal or diffuse brain atrophy in CT scans following chronic CS 2 exposure was also documented in previous reports 6,7,20,21) . A MRI study was performed by Peters et al 5) , who showed a pattern of central demyelinization in two out of four CS 2 -poisoned patients.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…In the patient described, both CT and MRI showed a picture of diffuse and progressive encephalic atrophy which was particularly pronounced in the cerebellum, according with the clinical picture. Focal or diffuse brain atrophy in CT scans following chronic CS 2 exposure was also documented in previous reports 6,7,20,21) . A MRI study was performed by Peters et al 5) , who showed a pattern of central demyelinization in two out of four CS 2 -poisoned patients.…”
supporting
confidence: 79%
“…A MRI study was performed by Peters et al 5) , who showed a pattern of central demyelinization in two out of four CS 2 -poisoned patients. Huang et al 21) described ten viscose rayon workers with polyneuropathy and neuropsychiatric disturbances: brain MRI abnormalities (mild cerebrocortical atrophy and/or multiple lesions of the basal ganglia and corona radiata) were present in seven of them. In the case reported by Frumkin 8) , MRI revealed advanced cerebellar atrophy and prominent atrophy in the posterior tracts and nuclei of the pons.…”
mentioning
confidence: 99%
“…Some also had chronic encephalopathy with abnormal computed tomography (CT) and magnetic resonance image (MRI) studies in the initial evaluation [21]. During the follow-up period, another 2 patients also developed an acute-onset stroke-like episode with hemiparesis and slurred speech.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Hageman et al [14], the brain MRI showed diffuse white matter hyperintensities, cerebral cortical atrophy, and mild enlargement of the ventricular system in 1 patient with long-term CS 2 exposure. In our previous studies [11, 12], multiple lacunar infarcts were noted in the subcortical white matter, basal ganglion, and even in the brain stem. Therefore, chronic encephalopathy with a small vessel disease was suggested [12].…”
Section: Discussionmentioning
confidence: 95%
“…The central toxicity of CS 2 can be characterized by cognitive dysfunction, emotional lability, parkinsonian features, cerebellar dysfunction, acute stroke-like symptoms, and atherosclerosis with dyslipidemia [8, 9, 10, 11, 12]. Brain computed tomography (CT) and magnetic resonance images (MRI) show focal or diffuse brain atrophy, and multiple brain lesions in the basal ganglia and subcortical white matter [8, 11, 12]. The data may indicate a small vessel disease.…”
Section: Introductionmentioning
confidence: 99%